PENGANGKATAN PEGAWAI NEGERI SIPIL DALAM JABATAN STRUKTURAL DI KABUPATEN BUNGO - Sari, Nirmala (Universitas Putra Indonesia YPTK Padang, 2015)
AbstrackPosition of Civil Servants in any government organization has a very important role,because the civil service is the backbone of the government in implementing nationaldevelopment. To be able to realize the implementation of governance and development tasksrequired of Civil Servants professional, responsible, honest, and fair conducted based systemswork performance and career system. But in the execution and implementation experiencedmany difficulties that require good governance, including in the process of appointment of theCivil Service to structural positions, because the position of the structural position issusceptible to irregularities or personal interests that dominate such political interests, familyrelatives and etc. Research on the Appointment of Civil Servants in structural positions inBungo done through regulatory approaches and theories associated with the fact that how theimplementation of personnel regulations in Bungo Regency, which is also called empirical legalresearch. Regulation of the barometer is Government Regulation Number 100 of 2000 onAppointment of Civil Servants in structural positions. Weak rule of law relating to sanction aviolation of article 6 of Government Regulation No. 100 of 2000 impacted prolonged among theCivil Service itself, to public services and the performance of Civil Servants in governmentBungo, among others, the emergence of apathy and egocentric subordinates to superiors as wellas other social reactions, which include behavior indifferent to duties as and unfair competitionamong fellow employees and others that eventually led to the Civil Service fragmented in mind.Keywords: Civil Servants; structural positions;